PELANGGARAN TERHADAP LARANGAN PERKAWINAN SETE’ DARAH PADA MASYARAKAT DAYAK KANAYATN DI DUSUN SENUNUK, DESA AGAK, KECAMATAN SEBANGKI, KABUPATEN LANDAK - NIM. A1011221076, ELMA BANYU PADASE (Jurnal Fatwa Hukum, 2026)
Abstract This research is entitled "VIOLATIONS OF THE BAN ON SETE’ DARAH MARRIAGE IN THE DAYAK KANAYATN COMMUNITY IN SENUNUK HALL, AGAK VILLAGE, SEBANGKI DISTRICT, LANDAK REGENCY". Sete’ darah marriage is a marriage that is prohibited in the Dayak Kanayatn customs, because this sete’ darah marriage is considered to have violated local customary provisions. If this sete’ darah marriage is carried out, the couple will receive the consequences of applicable customary law. The problem studied in writing this thesis is "How Violations of the Prohibition on Sete’ darah Marriage in the Dayak Kanayatn Community in Senunuk Hamlet, Agak Village, Sebangki District, Landak Regency". The purpose of this study is to determine violations of the prohibition on consanguineous marriage, the factors causing violations of the prohibition on consanguineous marriage, the legal consequences of violations of the prohibition on consanguineous marriage, and the efforts made by customary officials to prevent further violations of the prohibition on consanguineous marriage among the Dayak Kanayatn community in Senunuk Hamlet, Agak Village, Sebangki District, Landak Regency. This study uses an empirical research method and is descriptive in nature, namely legal research conducted through library research and direct field interviews. The results obtained in this study are: 1) Violations of the prohibition on consanguineous marriage among the Dayak Kanayatn community in Senunuk Hamlet are still carried out according to applicable customary provisions, even though the couple in question has committed a violation in the form of consanguineous marriage (one blood/incest); 2) Factors causing violations of the prohibition on consanguineous marriage among the Dayak Kanayatn community in Senunuk Hamlet are mutual love and personal desires, an increasingly open social environment, and social change and modernization. 3) The legal consequences of violating the prohibition on blood marriage are comprehensive, encompassing social, symbolic, and ritual aspects. These sanctions are implemented through various traditional rituals, such as the muang tulah (marriage), natar ka' panyugu (marriage), jalu cancakng (marriage), bakaramp (marriage), ngalih sintalahatn (marriage), and tampukng tawar (marriage). 4) Efforts by traditional officials include providing advice to continue preserving cultural traditions. It is necessary to increase awareness among the Dayak Kanayatn indigenous community in Senunuk Hamlet to obey and preserve customary provisions, especially those related to the prohibition of consanguineous marriage. Customs inherited from their ancestors must continue to be maintained and obeyed, by parents providing advice and understanding to children and the younger generation so that they grow up to respect and obey customary rules, so that similar violations do not occur again in the future. Keywords: Marriage, Sete’, Blood, Dayak, Kanayatn Abstrak Penelitian ini berjudul "PELANGGARAN TERHADAP LARANGAN PERKAWINAN SETE’ DARAH PADA MASYARAKAT DAYAK KANAYATN DI DUSUN SENUNUK, DESA AGAK, KECAMATAN SEBANGKI, KABUPATEN LANDAK". Perkawiann sete’ darah merupakan suatu perkawinan yang dilarang dalam adat istiadat Dayak Kanayatn, karena perkawinan sete’ darah ini dianggap telah melanggar ketentuan-ketentuan adat setempat. Jika perkawinan sete’ darah ini dilakukan, maka pasangan tersebut akan mendapatkan akibat hukum adat yang berlaku. Masalah yang diteliti dalam penulisan skripsi ini ialah “Bagaiman Pelanggaran Terhadap Larangan perkawinan Sete’ darah Pada Masyarakat Dayak Kanayatn Di Dusun Senunuk, Desa Agak, Kecamatan Sebangki, Kabupaten Landak”. Tujuan penelitian ini yaitu untuk mengetahui pelanggaran terhadap larangan perkawinan sete’ darah, faktor penyebab pelanggaran terhadap larangan perkawinan sete’ darah, akibat hukum pelanggaran terhadap larangan perkawinan sete’ darah, dan upaya yang dilakukan fungsionaris adat agar pelanggaran terhadap larangan perkawinan sete’ darah tidak terjadi lagi pada masyarakat Dayak Kanayatn di Dusun Senunuk, Desa Agak, Kecamatan Sebangki, Kabupaten Landak. Penelitian ini menggunakan metode penelitian Empiris dan sifat penelitian menggunakan sifat penelitian deskriptif, yaitu suatu penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka serta turun langsung kelapangan dengan cara wawancara. Hasil penelitian yang didapatkan dalam penelitian ini ialah : 1) pelanggaran terhadap larangan perkawinan dalam masyarakat Dayak Kanayatn di Dusun Senunuk tetap dilaksanakan berdasarkan ketentuan adat yang berlaku, meskipun pasangan yang bersangkutan telah melakukan pelanggaran berupa perkawinan sete darah (satu darah/incest); 2) Faktor penyebab terjadinya pelanggaran terhadap larangan perkawinan sete’ darah pada masyarakat Dayak Kanayatn di Dusun Senunuk ialah faktor saling cinta dan kehendak pribadi serta faktor kondisi lingkungan yang cenderung statis; 3) Akibat Hukum pelanggaran terhadap larangan perkawinan sete’ darah bersifat menyeluruh, baik secara sosial, simbolik, maupun ritual. Sanksi tersebut diwujudkan melalui berbagai ritual adat, seperti adat muang tulah, natar ka’ panyugu, jalu cancakng, bakaramp, ngalih sintalahatn, hingga tampukng tawar; 4) Upaya yang dilakukan fungsionaris adat memberikan nasihat untuk terus melestarikan adat budaya. Perlu ditingkatkannya kesadaran masyarakat adat Dayak Kanayatn di Dusun Senunuk untuk menaati dan melestarikan ketentuan adat, khususnya yang berkaitan dengan larangan perkawinan satu darah. Adat istiadat yang diwariskan oleh para leluhur perlu terus dijaga dan dipatuhi, dengan cara orang tua memberikan nasihat serta pemahaman kepada anak-anak dan generasi muda agar mereka tumbuh dengan menghargai serta mematuhi aturan adat, sehingga pelanggaran serupa tidak terjadi kembali di kemudian hari. Kata Kunci: Perkawinan, Sete’, Darah, Dayak, Kanayatn